2001
DOI: 10.1093/hmg/10.1.9
|View full text |Cite
|
Sign up to set email alerts
|

The kyphoscoliosis (ky) mouse is deficient in hypertrophic responses and is caused by a mutation in a novel muscle-specific protein

Abstract: The ky mouse mutant exhibits a primary degenerative myopathy preceding chronic thoraco-lumbar kyphoscoliosis. The histopathology of the ky mutant suggests that Ky protein activity is crucial for normal muscle growth and function as well as the maturation and stabilization of the neuromuscular junction. Muscle hypertrophy in response to increasing demand is deficient in the ky mutant, whereas adaptive fibre type shifts take place. The ky locus has previously been localized to a small region of mouse chromosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 28 publications
2
70
0
Order By: Relevance
“…3 The Ky gene was identified in 2001 by positional cloning, and a novel muscle-specific protein was identified. 5 The KY protein harbors a transglutaminase/protease domain, which is homologous to other proteins in the transglutaminase family, and it has been proposed to be a protease. 5,6 However, multiple alignment with proteins belonging to the transglutaminase superfamily showed that a group of transglutaminase proteins including KY lack the enzymatic active site triad of amino acids, and the protease function has been questioned.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…3 The Ky gene was identified in 2001 by positional cloning, and a novel muscle-specific protein was identified. 5 The KY protein harbors a transglutaminase/protease domain, which is homologous to other proteins in the transglutaminase family, and it has been proposed to be a protease. 5,6 However, multiple alignment with proteins belonging to the transglutaminase superfamily showed that a group of transglutaminase proteins including KY lack the enzymatic active site triad of amino acids, and the protease function has been questioned.…”
Section: Discussionmentioning
confidence: 99%
“…5 The KY protein harbors a transglutaminase/protease domain, which is homologous to other proteins in the transglutaminase family, and it has been proposed to be a protease. 5,6 However, multiple alignment with proteins belonging to the transglutaminase superfamily showed that a group of transglutaminase proteins including KY lack the enzymatic active site triad of amino acids, and the protease function has been questioned. 13,18 Futher studies indicates that KY should be considered to be a Z-discassociated structural protein that interacts with sarcomeric partners such as filamin C (FLNC), myosin binding protein C, slow type (MYBPC1), KY interacting protein 1 (KYIP1, IGFN1) and titin (TTN).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations